METHODS OF SYNTHESIS ENERGY SUPPLY ELECTIC ENGINE UNMANNED AERIAL VEHICLE - Казак, В.; Горбач, О. (Science-based technologies, 2011)
Direct current motors main types are considered. The analysis of the main methods of control DC motors is held. The basic relations used in the direct current motor management are showing. The methods of speed control motor as the drive screws main component of unmanned aerial vehicles are analyzed. Calculations of the solar cell parameters as a source of propulsion power unmanned aerial vehicle are given.